Grønlands særlige foranstaltningsdømte.: En kortlægning - Rømer, Mette; Lauritsen, Annemette Nyborg (Grønlandsk Kultur- og Samfundsforskning, 2024)
Unlike legal systems in Denmark or many other countries, the Greenlandic Penal Code does not include the concept of punishment. Instead, the Code contains several diverse sanctions intended to prevent reoffences through treatment. This article explores this particular legal structure by examining cases of Greenlandic citizens sanctioned for treatment with or without deprivation of liberty. Based on an archival study of records held by the Prosecutor’s Office of the Greenland Police, this article maps the number of Greenlandic citizens sanctioned for treatment with or without deprivation of liberty in either Greenland or Denmark along with the assessment of their mental state and place of treatment. The findings show that 49 of the 160 individuals convicted were sent to Denmark for treatment and rehabilitation within the prison service, forensic psychiatry, or forensic intellectual disability services. The most common types of crime among the convicted were violent. This article recommends that a new registration practice is needed to methodologically generate a representative picture of the convicted population.